2001
DOI: 10.1002/dvdy.1130
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation in the embryonic myocardium by A1 adenosine receptor activation

Abstract: A1 adenosine receptors (A1ARs) are expressed in the embryonic heart and influence cardiac function at early developmental stages. To test if A1ARs also affect cardiac structural development, we examined the effects of A1AR activation on heart formation. When pregnant mice were treated with the A1AR agonist, N 6 -cyclopentyladenosine (CPA), fetuses showed marked reduction of ventricular size and manifested features of heart failure. Suggesting that these findings represent direct effects on embryos, CPA treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Mouse embryos dissected at 8-8.5 dpc were cultured using the roller system, as described (11,12). Embryos were cultured, six per 60-ml bottle, at 38°C for 48 h in 5 ml of rat serum to reach the 9.5-to 10-dpc developmental stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse embryos dissected at 8-8.5 dpc were cultured using the roller system, as described (11,12). Embryos were cultured, six per 60-ml bottle, at 38°C for 48 h in 5 ml of rat serum to reach the 9.5-to 10-dpc developmental stage.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether NRG-1 was capable of inducing ectopic lacZ expression within the context of intact, developing embryos, we isolated 8-to 8.5-dpc CCS-lacZ embryos and cultured them for 48 h by using techniques described (11,12), in the presence or absence of NRG-1. NRG-1-treated embryos seemed similar to control embryos on gross examination, and both had reached the 9.5-10.0 dpc developmental stage (Fig.…”
Section: Nrg-1 Induces Ectopic Ccs Formation In Treatment Of Whole Emmentioning
confidence: 99%
“…The mechanisms for causing these cardiac defects remain to be well deciphered. Several studies on G protein coupled receptors (Yanagisawa et al, 1998;Nebigil et al, 2000;Zhao and Rivkees, 2001), growth factor receptors (Gaussin et al, 2002), and intracellular signal mediators (Jaber et al, 1996;Koera et al, 1997;Kuwahara et al, 1999;Wei et al, 2002) have shown hypoplastic myocardium and trabeculae in the heart. In these cases, either cell proliferation or apoptosis is found to be associated with the phenotypes, suggesting that myocardium development is regulated by various signaling systems and different mechanisms.…”
Section: Figmentioning
confidence: 99%
“…The parietal yolk sac was removed by using a pair of fine forceps and the visceral yolk sac was left intact. Embryos (2-5/bottle) were cultured in 5 ml of rat serum at 38°C in 30 rev/min rotation in the roller bottle system (Sturm and Tam, 1993;Wei et al, 2001;Zhao and Rivkees, 2001). Embryos were treated with vehicle or Y27632 (Calbiochem), a selective ROCK kinase inhibitor Iwamoto et al, 2000;Narumiya et al, 2000).…”
Section: Experimental Procedures Embryo and Heart Culturementioning
confidence: 99%
“…Increased activation of A 1 AR leads to reduced heart rates in embryonic hearts (13). Activation of A 1 ARs in embryos has also been observed to reduce myocyte proliferation (14). As the fetus matures, A 1 AR expression becomes greater in the atria than the ventricles, and A 1 AR expression persists in the heart throughout adulthood (11).…”
mentioning
confidence: 99%